Six New Species of Tomentella (Thelephorales, Basidiomycota) From Tropical Pine Forests in Central Vietnam - Lu, Xu; Cao, Ting; Nguyễn, Trang Thị Thu; Yuan, Hai-Sheng (Frontiers in Microbiology, 2022)
Up to this point, studies on the taxonomy and phylogeny of the basidiomycetous genus Tomentella stemmed mainly from the temperate to boreal zones of the Northern hemisphere, but were scarce in tropical Asia. In this study, six new species T. bidoupensis, T. brevisterigmata, T. cinereobrunnea, T. longiechinula, T. stipitobasidia and T. verruculata from central Vietnam in Southeast Asia, are de-scribed and illustrated based on morphological characteristics and molecular phylogenetic analyses of the nuclear ribosomal ITS (internal transcribed spacer: ITS1-5.8S-ITS2) and LSU (large sub-unit: 28S) markers. Maximum likelihood and Bayesian analyses were used to confirm the phylogenetic positions of these new species and all of them can be well recognized by the macroscopical and anatomical characteristics. The new species and closely related species in the phylogenetic tree, and the new species and morphologically similar species are discussed, while the host plant for these new species were speculated based on the phylogenetic analyses and the tree species information of the investigated forests.